2000
DOI: 10.1086/302997
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting of Human GRB10 and Its Mutations in Two Patients with Russell-Silver Syndrome

Abstract: Documentation of maternal uniparental disomy of chromosome 7 in 10% of patients with Russell-Silver syndrome (RSS), characterized by prenatal and postnatal growth retardation and dysmorphic features, has suggested the presence of an imprinted gene on chromosome 7 whose mutation is responsible for the RSS phenotype. Human GRB10 on chromosome 7, a homologue of the mouse imprinted gene Grb10, is a candidate, because GRB10 has a suppressive effect on growth, through its interaction with either the IGF-I receptor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
2
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 52 publications
1
54
2
3
Order By: Relevance
“…No imprinted QTL had been previously reported in this chromosomal region in pigs. Yet, several imprinted genes related with early growth and development [6,26,35,37] have been reported in the orthologous region of the human genome (7q11-q22; see comparative mapping at http://www.toulouse.inra.fr/lgc/pig/compare). This unique evidence of imprinting contrasts with the numerous reports of imprinting effects in pigs recently published.…”
Section: Imprintingmentioning
confidence: 99%
“…No imprinted QTL had been previously reported in this chromosomal region in pigs. Yet, several imprinted genes related with early growth and development [6,26,35,37] have been reported in the orthologous region of the human genome (7q11-q22; see comparative mapping at http://www.toulouse.inra.fr/lgc/pig/compare). This unique evidence of imprinting contrasts with the numerous reports of imprinting effects in pigs recently published.…”
Section: Imprintingmentioning
confidence: 99%
“…Cette protéine, impliquée dans la voie de signalisation de l'IGF-1, se lie par son domaine GYF à la protéine adaptatrice Grb10, ce complexe interagissant avec les récepteurs IGF-1 via le domaine SH 2 de Grb10 (Figure 1). La résultante de cette interaction est l'inhibition de la phosphorylation sur tyrosine des substrats IRS (insulin responsive substrate), mais également le blocage concomitant de l'accès aux phosphatases, mettant ainsi les récepteurs dans un état actif latent [11][12][13]. L'implication de ce méca-nisme dans la pathologie reste inconnue.…”
Section: Ide (Insulin Degrading Enzyme) Et Maladie D'alzheimerunclassified
“…L'implication de ce méca-nisme dans la pathologie reste inconnue. Cependant, le rôle spécifique de la protéine adaptatrice Grb10 dans le développement neurologique a déjà été suggéré par la découverte de mutations pathogènes dans le syndrome de Silver -Russell, qui associe un retard de croissance intra-utérin et un retard du développement psychomoteur ou du langage [13]. Notre étude du gène GIGYF2 par séquençage direct dans 249 cas familiaux (italiens et français) de la maladie de Parkinson et 227 témoins nous a permis d'identifier une mutation (faux-sens) du gène GIGYF2 chez 6 % des sujets atteints de maladie de Parkinson [14].…”
Section: Ide (Insulin Degrading Enzyme) Et Maladie D'alzheimerunclassified
“…Spontaneous growth rates in these children correlated with measures of insulin secretion [31]and thus the primary abnormality in these severe SGA children may be a reduced β-cell mass and inability to produce sufficient insulin secretion to achieve catch-up in weight or height. Study of the severe intrauterine growth retarded Russell-Silver syndrome has shown genetic defects in GRB10 [35], which encodes an important mediator of IGF-I and insulin receptor signalling. It is possible that primary abnormalities in IGF-I signalling underlie the apparent IGF-I resistance and may contribute to reduced β-cell mass and poor postnatal growth of these SGA children.…”
Section: Risk Of Type 2 Diabetes In Infants Born Small For Gestationamentioning
confidence: 99%